Adverse selection, heterogeneous beliefs, and evolutionary learning - Clemens Buchen; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2021)
We relax the common assumption of homogeneous beliefs in principal-agent relationships with adverse selection. Principals are competitors in the product market and write contracts also on the base of an expected aggregate. The model is a version of a cobweb model. In an evolutionary learning set-up, which is imitative, principals can have different beliefs about the distribution of agents' types in the population. The resulting nonlinear dynamic system is studied. Convergence to a uniform belief depends on the relative size of the bias in beliefs.
Keywords: C61; C73; D82; D83; E32; 330; Evolutionary game theory; imitation equilibrium; heterogeneous beliefs; adverse selection; cobweb model